Factors Influencing Customers’ Purchase Decision Making On Halal Cosmetic Product - Ovalia Rukmana; Puspita Febrianti (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – This study aims to investigate factors which influence customers’ purchasing decisions on halal cosmetic product, called Wardah. Methodology/approach – Quantitative Approach is adopted in this study. A survey was conducted with 100 respondents to grasp the respondents’ perceptions and attitude on factors that influence them to make purchase decision on halal cosmetic product (Wardah). Purposive sampling technique is employed to determine the sample of respondents. For data analysis, we conducted multiple linear regression, with SPSS. Findings – As a result, this study indicates that factors influencing the customers’ purchasing decision making on halal cosmetic (Wardah) are the variables of product quality, price and brand image. Those variables have positive and significant influence to the customers’ purchasing decision. Novelty/value – this study reveals motivating factors on customers purchasing decision making on halal cosmetics in Indonesia.